Exploring Code-Switching Practices in Vietnamese Classrooms: An Introductory Investigation - Nguyen Thi Dan Tam (CV. Rustam, 2024)
This study delves into the nuanced practice of code-switching (CS) in English as a Foreign Language (EFL) classrooms in Vietnam, examining its implications for language learning from both educators' and learners' perspectives. Through a mixed-methods approach, involving surveys and interviews with 225 ESL students and 8 experienced ESL lecturers at a renowned public university in Ho Chi Minh City, this research illuminates the multifaceted role of CS in enhancing comprehension, engagement, and linguistic proficiency. The findings reveal a general preference among students for a balanced use of English and Vietnamese, underscoring the pedagogical value of strategic CS in facilitating understanding and reducing the affective filter in language learning. Educators' narratives highlight the benefits and challenges of CS in maintaining English exposure while accommodating diverse learner needs. The study also uncovers emerging issues, such as the impact of digital and online learning environments on CS practices and the influence of external expectations on educators' language use decisions. By integrating insights from existing literature, this research contributes to a deeper understanding of the dynamic interplay between language use and educational outcomes in bilingual settings, advocating for flexible, learner-centered teaching approaches that accommodate the evolving landscape of language education.